Helpful social support for chronic pain in long‐term care residents: "With a little help I manage on my own" - Marta Osório deMatos; Sónia Figueira Bernardes (Wiley, 2023)
Abstract Aims and Objectives To understand older adults' experiences of receiving formal pain‐related social support and to identify which caregivers' responses are perceived as (un)helpful to chronic pain adjustment. Background Chronic pain is highly prevalent in long‐term care residents, negatively impacting their psychological, physical and social functioning. However, research has lacked to address the extent to which residents' experiences with staff responses, to their pain, may influence chronic pain outcomes. Design Qualitative study. Methods Twenty‐nine older adults (7 men, 22 women, Mage = 87.7) were interviewed online through semi‐structured interviews, and a thematic analysis was conducted. COREQ guidelines were followed. Results Two main themes emerged: (1) support during a pain crisis aiming at its relief and (2) support with daily activities because of pain to overcome pain interference. Findings indicate pain‐related support is helpful when residents feel their psychological and functional autonomy is protected, and the interactions convey connection and intimacy. Furthermore, residents actively try to shape the support to be received. Also, gender roles and expectations seem to influence pain‐related supportive interactions. Conclusion Pain‐related social support may contribute to the maintenance of older adults' health status and autonomy, ensuring a fulfilling and healthy aging process despite chronic pain. Relevance to Clinical Practice Findings can inform effective pain‐related care practices in long‐term care, regarding (1) how residents can shape the support they need; (2) which kind of support should be provided, and (3) how caregivers and organizations should provide pain‐related support. Patient or Public Contribution Older adults who participated in the study were recruited from 3 long‐term care facilities in Lisbon, in which they resided for longer than 3 months, had persistent/intermittent pain for more than 3 months; were able to maintain a conversation, recollect real episodes, and to fully provide informed consent to participate.